(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
The article deal with the issue of same?sex unions in the Italian legal system. The absence of a complete legislative framework concerning the rights of same-sex couples has determined several jurisdictional interventions, by ordinary judges, by the Court of Cassation and by the Constitutional Courts. Regulating same?sex unions is relevant not only with regards to the legal positions of the two individuals in the relationship, but also in the perspective of access to adoption, step?child adoption or even artificial reproductive technologies, on which the Constitutional Court has recently intervened.